Non-Verbal Cues: Improving Communication in Construction Projects - Doğan, Sevgi Zeynep; Gunhan,S.; Senol,G.; Dogan,S.Z. (American Society for Engineering Education, 2012)
Construction industry is a dynamic, project based industry in where many problems occur due to communication issues. As it is proven that effective communication and conflict resolution abilities have a strong correlation between them, communication in the construction industry should constantly be improved. Unfortunately, the existing construction curricula do not offer enough courses which would help students to communicate effectively. Embedding technical communication into curricula and introducing courses such as Construction Communication aiming on producing construction management (CM) graduates with good writing and speaking skills are necessary. However, written and verbal languages are not the sole means by which individuals exchange information. Non-verbal cues play a significant role in communication. Therefore it is necessary for CM graduates to master the skills of using and reading body language. The literature study for the subject of communication in the education shows that body language and non-verbal communication were not taken into consideration yet. They are primarily the subject areas of anthropologists, linguists, and social psychologists. This paper aims reviewing the role of non-verbal communication skills in construction business and highlights the importance of bringing the topic into classroom. © 2012 American Society for Engineering Education.
Keywords: [No Keyword Available]